The genome sequence of celery (Apium graveolens L.), an important leaf vegetable crop rich in apigenin in the Apiaceae family. (6th January 2020) - Li, Meng-Yao; Feng, Kai; Hou, Xi-Lin; Jiang, Qian; Xu, Zhi-Sheng; Wang, Guang-Long; Liu, Jie-Xia; Wang, Feng; Xiong, Ai-Sheng
Abstract: Celery ( Apium graveolens L.) is a vegetable crop in the Apiaceae family that is widely cultivated and consumed because it contains necessary nutrients and multiple biologically active ingredients, such as apigenin and terpenoids. Here, we report the genome sequence of celery based on the use of HiSeq 2000 sequencing technology to obtain 600.8 Gb of data, achieving ~189-fold genome coverage, from 68 sequencing libraries with different insert sizes ranging from 180 bp to 10 kb in length. The assembled genome has a total sequence length of 2.21 Gb and consists of 34, 277 predicted genes. Repetitive DNA sequences represent 68.88% of the genome sequences, and LTR retrotransposons are the main components of the repetitive sequences. Evolutionary analysis showed that a recent whole-genome duplication event may have occurred in celery, which could have contributed to its large genome size. The genome sequence of celery allowed us to identify agronomically important genes involved in disease resistance, flavonoid biosynthesis, terpenoid metabolism, and other important cellular processes. The comparative analysis of apigenin biosynthesis genes among species might explain the high apigenin content of celery. The whole-genome sequences of celery have been deposited at CeleryDB (http://apiaceae.njau.edu.cn/celerydb ). The availability of the celery genome data advances our knowledge of the genetic evolution of celery and will contribute to further biological research and breeding in celery as well as other Apiaceae plants.